Study on production and logistics in the industrialization of drinking water from a company located in the Andes mountain ranges - Bueno, Wagner Pietrobelli; Godoy, Leoni Pentiado; Wegner, Roger da Silva; Godoy, Taís Pentiado (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aims to analyze the production and logistics processes, aimed at a water bottling company, where its raw material is through thawing in the mountains of the Andes mountain ranges. Therefore, water is a natural resource responsible for the origin of life, too, is water that sustains, animals, plants, ie, is the basic requirement for sustaining the planet. It can be said that the shortage of water being global leadership is caused by environmental devastation and pollution of the planet. The fundamental question of this research is the logistics process for the distribution of this valuable natural resource to the world. Therefore, the industrialization of drinking water unites technological factors and logistics concepts emphasizing the operational strategy in place with interacting function between suppliers and customers. The current global scenario has required the responses from companies and fast and accurate decisions of its business in the pursuit of competitiveness.